Cross-linked polyisobutylene composite material with high efficiency self-catalysis at room temperature, its preparation method and application in pipe material

CN122898071APending Publication Date: 2026-10-13ZHEJIANG AKAN IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611133172.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2026-05-25
Filing Date
2026-07-29
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

但XPAP2(交联聚乙烯/铝合金/交联聚乙烯复合管)也有缺点,如采用硅烷接枝的聚乙烯和二月桂酸二丁基锡催化剂为原料生产,产品下线后需要放入交联房向管材内部通热水(95-100℃),循环通热水12h以上才能达到GB/T 18997.2-2020 中交联度65的指标

Benefits of technology

传统交联聚乙烯复合管需要通95-100℃的热水或蒸汽12h以上才能达到交联度65的要求,本发明的室温下高效自催化的交联聚异丁烯复合料制备的复合管(交联聚异丁烯/铝合金/交联聚异丁烯复合管)的产品结构和传统交联聚乙烯复合管一样,但材料性能更好,生产的产品下线后在室温可以高效自催化交联,不需要通热水或通蒸汽催化交联,自然存放12h即可达到GB/T18997.2-2020 中交联度65的要求,且产品使用温度更高,性能更优异,大大节约了能耗,降低了生产成本,提升了生产效率,且产品使用温度提升20℃,可以用于温度大于110℃的特殊领域,适用于工况要求更高的领域。此外,本发明产品的承压能力更强,用水更安全,应用前景良好。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898071A_ABST
    Figure CN122898071A_ABST
Patent Text Reader

Abstract

The application provides a room-temperature high-efficiency self-catalytic crosslinked polyisobutylene composite material and a preparation method and application in pipe materials, relates to the technical field of pipe materials, and the room-temperature high-efficiency self-catalytic crosslinked polyisobutylene composite material is used for preparing a composite pipe, the product structure is the same as that of a traditional crosslinked polyethylene composite pipe, but the material performance is better, the product can be efficiently self-catalytically crosslinked at room temperature after being produced and discharged, does not need to be catalytically crosslinked by passing hot water or steam, the crosslinking degree is greater than 65 after being naturally stored for 12 hours, the product has a higher use temperature and more excellent performance, energy consumption is greatly saved, production cost is reduced, and production efficiency is improved, the product use temperature is increased by 20 DEG C, can be used in special fields with a temperature greater than 110 DEG C, and is suitable for fields with higher working conditions. In addition, the product has stronger pressure-bearing capacity, is safer to use with water, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of pipe technology, and in particular to a highly efficient self-catalyzing cross-linked polyisobutylene composite material at room temperature, its preparation method, and its application in pipes. Background Technology

[0002] In modern building hot and cold water and heating systems, aluminum-plastic composite pipes, combining the pressure resistance of metal with the corrosion resistance of plastic, have become one of the important pipe materials to replace traditional galvanized steel pipes. According to GB / T18997.2-2020 "Aluminum-Plastic Composite Pressure Pipes Part 2: Aluminum Pipe Butt-Welded Aluminum-Plastic Pipes" standard, these pipes typically adopt a five-layer composite structure of "plastic-hot melt adhesive-aluminum alloy-hot melt adhesive-plastic". The standard mainly classifies four mainstream products, which have significant differences in temperature resistance and applicable scenarios due to the different materials of the inner and outer plastic layers. The mainstream products are PAP1 (polyethylene / aluminum alloy / heat-resistant polyethylene composite pipe), RPAP3 (heat-resistant polyethylene / aluminum alloy / heat-resistant polyethylene composite pipe), PPAP4 (random polypropylene / aluminum alloy / random polypropylene composite pipe), and XPAP2 (cross-linked polyethylene / aluminum alloy / cross-linked polyethylene composite pipe). The above four are ordinary five-layer composite pipes, with each two layers bonded by hot melt adhesive, and their heat resistance temperature is limited.

[0003] PAP1 (polyethylene / aluminum alloy / heat-resistant polyethylene composite pipe), RPAP3 (heat-resistant polyethylene / aluminum alloy / heat-resistant polyethylene composite pipe), and PPAP4 (random polypropylene / aluminum alloy / random polypropylene composite pipe) are three types of pipes that rely on hot melt adhesive bonding, and their long-term operating temperature is usually limited to below 70℃. Although they can meet general heating needs, they are limited by the heat creep resistance of polyethylene (PE) and random copolymer polypropylene (PP-R), and are at risk of aging under high-temperature and pressure conditions. XPAP2 (cross-linked polyethylene / aluminum alloy / cross-linked polyethylene composite pipe) is currently a high-end product among five-layer composite pipes. By upgrading the inner and outer layers to cross-linked polyethylene (PEX), its macromolecular chains are transformed from a linear structure to a three-dimensional network structure, which increases the long-term operating temperature of the pipe to 95℃, and the short-term extreme temperature resistance can reach about 100℃. This material advantage makes it irreplaceable in solar water heating systems, high-temperature underfloor heating, and industrial heat exchange pipes. However, XPAP2 (cross-linked polyethylene / aluminum alloy / cross-linked polyethylene composite pipe) also has disadvantages. For example, it is produced using silane-grafted polyethylene and dibutyltin dilaurate catalyst as raw materials. After the product comes off the production line, it needs to be placed in a cross-linking chamber and hot water (95-100℃) needs to be circulated inside the pipe for more than 12 hours to achieve the cross-linking degree of 65 in GB / T 18997.2-2020. Because it requires continuous hot water catalysis for cross-linking, the entire production process has high energy consumption and a slow production cycle. Summary of the Invention

[0004] In view of this, the present invention proposes a highly efficient self-catalytic cross-linked polyisobutylene composite material at room temperature, its preparation method and its application in pipes, thereby solving the above problems.

[0005] The technical solution of this invention is implemented as follows: A highly efficient self-catalyzing cross-linked polyisobutylene composite material at room temperature, comprising silane-grafted polyisobutylene and a room-temperature cross-linking catalyst in a mass ratio of 85-95:3-8; The silane-grafted polyisobutylene comprises, by weight, the following raw materials: 87-97 parts polyisobutylene resin, 1.05-3.0 parts graft modifier, 0.03-0.10 parts initiator, 2.0-5.0 parts antioxidant, 1.33-3.38 parts brightener, and 0.03-0.30 parts polymerization inhibitor. The room temperature crosslinking catalyst comprises, by weight, the following raw materials: 80-95 parts polyisobutylene resin, 3.0-5.0 parts antioxidant, 1.3-4.5 parts lubricant, 0.05-0.30 parts catalyst, 0.01-0.05 parts catalyst promoter and 0.05-0.16 parts hydrophilic agent.

[0006] The catalyst is dioctyltin dilaurate, and the catalyst promoter is tetramethylguanidine.

[0007] Furthermore, the grafting modifier is trimethoxyvinylsilane / vinyltriisopropoxysilane and isopropyltris(dioctylpyrophosphate)titanate in a mass ratio of 0.05-1.5:1-1.5. The initiator is di-tert-butylperoxyisopropylbenzene or 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane.

[0008] Furthermore, the antioxidant is a mixture of tris[2,4-di-tert-butylphenyl] phosphite and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] in a mass ratio of 1:1; The brightener is high-density oxidized polyethylene wax, low molecular weight polytetrafluoroethylene micro powder, and zinc stearate in a mass ratio of 0.5-1.5:0.03-0.08:0.8-1.8.

[0009] Furthermore, the polymerization inhibitor is hydroquinone or tert-butylcatechol; The lubricant is high-density oxidized polyethylene wax and zinc stearate in a mass ratio of 0.1-2:1.2-2.5.

[0010] Furthermore, the hydrophilic agent is glycerol and sodium sulfate (5000 mesh or finer) in a mass ratio of 2-8:3-8.

[0011] Furthermore, the preparation method of the silane-grafted polyisobutylene is as follows: polyisobutylene resin, graft modifier, initiator, antioxidant, brightener and polymerization inhibitor are mixed and stirred, granulated in a parallel twin-screw extruder, and processed at a temperature of 190-210℃ to obtain silane-grafted polyisobutylene.

[0012] Furthermore, the preparation method of the room temperature crosslinking catalyst is as follows: polyisobutylene resin is ground to a fineness of 60 mesh or higher, then mixed with antioxidant, lubricant, dioctyltin dilaurate, tetramethylguanidine and hydrophilic agent, dried at 80-85℃ for 1-2 hours, and then granulated in a parallel twin-screw extruder at a processing temperature of 150-180℃ to obtain the room temperature crosslinking catalyst.

[0013] A method for preparing a highly efficient self-catalyzing cross-linked polyisobutylene composite at room temperature includes the following steps: mixing silane-grafted polyisobutylene and a room-temperature cross-linking catalyst in a mass ratio of 85-95:3-8 and extruding the mixture in a single-screw extruder.

[0014] Application of a highly efficient, self-catalytic cross-linked polyisobutylene composite material at room temperature in pipes.

[0015] Furthermore, the manufacturing process of the pipe is as follows: First layer: Cross-linked polyisobutylene composite material is extruded into a core tube; Second layer: After heating the core tube at 100℃ for 20 seconds, coat the surface with maleic anhydride-grafted polybutene hot melt adhesive with a thickness of 0.1-0.15mm. Third layer: The aluminum strip is rolled into a tube shape, wrapped on the hot melt adhesive of the second layer, and then formed into an aluminum tube by laser butt welding. Fourth layer: After the aluminum tube is heated by high frequency, maleic anhydride grafted polybutene hot melt adhesive is coated on the outer surface with a thickness of 0.1-0.15mm. Fifth layer: Cross-linked polyisobutylene composite material is used as the outer tube material, coated on the hot melt adhesive of the fourth layer, and then cooled and shaped to form a composite tube. After being corona treated, the composite pipes are inkjet printed and coiled to form finished products. After being stored naturally for 12 hours, the degree of cross-linking is greater than 65%.

[0016] Compared with the prior art, the beneficial effects of the present invention are: Traditional cross-linked polyethylene composite pipes require hot water or steam at 95-100℃ for more than 12 hours to achieve the required degree of cross-linking of 65%. The composite pipe (cross-linked polyisobutylene / aluminum alloy / cross-linked polyisobutylene composite pipe) prepared by this invention using a highly efficient, self-catalyzing cross-linked polyisobutylene composite material at room temperature has the same product structure as traditional cross-linked polyethylene composite pipes, but with superior material properties. After production, the product can efficiently undergo self-catalyzing cross-linking at room temperature without the need for hot water or steam. It reaches the required degree of cross-linking of 65 as specified in GB / T18997.2-2020 after only 12 hours of natural storage. Furthermore, the product has a higher operating temperature and superior performance, significantly saving energy, reducing production costs, and improving production efficiency. The operating temperature is increased by 20℃, allowing it to be used in special fields with temperatures exceeding 110℃, making it suitable for applications with higher requirements. In addition, the product of this invention has stronger pressure resistance, is safer to use, and has promising application prospects. Attached Figure Description

[0017] Figure 1 The polyisobutylene resin of this invention.

[0018] Figure 2 The present invention refers to the room temperature crosslinking catalyst mixture before and after granulation.

[0019] Figure 3 The present invention relates to a cross-linked polyisobutylene / aluminum alloy / cross-linked polyisobutylene composite pipe. Detailed Implementation

[0020] To better understand the technical content of this invention, specific embodiments are provided below to further illustrate the invention.

[0021] Unless otherwise specified, the experimental methods used in the embodiments of this invention are all conventional methods.

[0022] Unless otherwise specified, all materials and reagents used in the embodiments of this invention are commercially available.

[0023] The grafting modifier of the present invention is trimethoxyvinylsilane / vinyltriisopropoxysilane and isopropyltris(dioctylpyrophosphate)titanate in a mass ratio of 0.05-1.5:1-1.5; or vinyltriisopropoxysilane and isopropyltris(dioctylpyrophosphate)titanate in a mass ratio of 0.05-1.5:1-1.5; the grafting modifier used in the examples is trimethoxyvinylsilane and isopropyltris(dioctylpyrophosphate)titanate in a mass ratio of 0.5:1.2.

[0024] The initiator of this invention is di-tert-butylperoxyisopropylbenzene or 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane; the di-tert-butylperoxyisopropylbenzene used in the examples.

[0025] The antioxidant of the present invention is tris[2,4-di-tert-butylphenyl] phosphite and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] in a mass ratio of 1:1.

[0026] The brightener of the present invention is high-density oxidized polyethylene wax, low molecular weight polytetrafluoroethylene micro powder and zinc stearate in a mass ratio of 0.5-1.5:0.03-0.08:0.8-1.8; the brightener used in the examples is high-density oxidized polyethylene wax, low molecular weight polytetrafluoroethylene micro powder and zinc stearate in a mass ratio of 1:0.05:1.3.

[0027] The polymerization inhibitor of the present invention is hydroquinone or tert-butylcatechol; the polymerization inhibitor used in the examples is hydroquinone.

[0028] The lubricant of the present invention is high-density oxidized polyethylene wax and zinc stearate in a mass ratio of 0.1-2:1.2-2.5; the lubricant used in the examples is high-density oxidized polyethylene wax and zinc stearate in a mass ratio of 1:2.

[0029] The hydrophilic agent of the present invention is glycerol and sodium sulfate (5000 mesh or higher) in a mass ratio of 2-8:3-8. In the examples, the hydrophilic agent used is glycerol and sodium sulfate (5000 mesh or higher) in a mass ratio of 3:5.

[0030] The raw materials used in this invention and their sources are shown in the table below.

[0031] Preparation Example 1 Silane-grafted polyisobutylene, by weight, comprises the following raw materials: 90 kg polyisobutylene resin, 2.7 kg graft modifier, 0.1 kg initiator, 2 kg antioxidant, 2.35 kg brightener and 0.1 kg polymerization inhibitor. The above-mentioned method for preparing silane-grafted polyisobutylene is as follows: polyisobutylene resin, grafting modifier, initiator, antioxidant, brightener and polymerization inhibitor are mixed and stirred, granulated in a parallel twin-screw extruder, and processed at a temperature of 200℃ to obtain silane-grafted polyisobutylene.

[0032] Preparation Example 2 The room temperature crosslinking catalyst, by weight, comprises the following raw materials: 90 kg polyisobutylene resin, 3 kg antioxidant, 3 kg lubricant, 0.1 kg dioctyltin dilaurate, 0.03 kg tetramethylguanidine, and 0.08 kg hydrophilic agent.

[0033] The preparation method of the above-mentioned room temperature crosslinking catalyst is as follows: Polyisobutylene resin is ground to 60 mesh or higher using a grinding mill, and then mixed with antioxidant, lubricant, dioctyltin dilaurate, tetramethylguanidine and hydrophilic agent. After drying at 80°C for 1 hour, it is granulated in a parallel twin-screw extruder at a processing temperature of 170°C to obtain the room temperature crosslinking catalyst.

[0034] Example The manufacturing process of cross-linked polyisobutylene / aluminum alloy / cross-linked polyisobutylene composite pipe is as follows: First layer: Core tube extrusion: 90 kg of silane-grafted polyisobutylene and 5 kg of room temperature crosslinking catalyst are mixed evenly and extruded in a single screw extruder and cooled to form the core tube. Second layer: After heating the core tube in an oven at 100℃ for 20 seconds, coat the surface with a 0.1mm thick maleic anhydride-grafted polybutene hot melt adhesive. Third layer: The aluminum strip is rolled into a tube shape, wrapped on the hot melt adhesive of the second layer, and then formed into an aluminum tube by laser butt welding. Fourth layer: After the aluminum tube is subjected to high-frequency heating (frequency is 3 kHz, tube heating time is 5 seconds, aluminum tube temperature is 180±2℃, and tube surface temperature after heating is 80±2℃), a 0.1 mm thick maleic anhydride grafted polybutene hot melt adhesive is coated on the outer surface. Fifth layer: Outer tube extrusion: 90 kg of silane-grafted polyisobutylene and 5 kg of room temperature crosslinking catalyst are mixed evenly and extruded in a single screw extruder, coated on the hot melt adhesive of the fourth layer, and then cooled and shaped to prepare a composite tube. Finally, the composite pipes are corona treated, then inkjet printed and coiled to become finished products.

[0035] Comparative Example 1 The difference between this comparative example and the embodiment is that silane-grafted polyisobutylene is replaced with polyisobutylene, while the rest is the same as the embodiment.

[0036] Comparative Example 2 The difference between this comparative example and the embodiment is that silane-grafted polyisobutylene is replaced with silane-grafted polyethylene; otherwise, they are the same as in the embodiment.

[0037] Comparative Example 3 The difference between this comparative example and the embodiment is that dioctyltin dilaurate is replaced with dibutyltin dilaurate in the room temperature crosslinking catalyst; otherwise, they are the same as in the embodiment.

[0038] Comparative Example 4 The difference between this comparative example and the example is that the room temperature crosslinking catalyst lacks tetramethylguanidine; otherwise, they are the same as the example.

[0039] Test Example 1 According to testing, the degree of crosslinking of the finished product of this embodiment of the invention is 72 after being stored naturally for 12 hours.

[0040] The crosslinking degree of the finished product in Comparative Example 1 was 0 because ordinary polyisobutylene resin did not undergo a grafting reaction, and its molecular chain did not have any crosslinkable active groups, so it could not undergo crosslinking.

[0041] The crosslinking degree of the finished product in Comparative Example 2 was 35%, mainly because the silane-grafted polyethylene molecular chain had fewer branches and a lower grafting degree, resulting in a low crosslinking degree in the final product. Meanwhile, the product of Comparative Example 2 had a very rough appearance, with uneven inner and outer walls, primarily due to the incompatibility between the silane-grafted polyethylene and the polyisobutylene in the catalyst, leading to delamination and a poor appearance. Furthermore, in the 95°C hydrostatic test, the pipe in the example failed at 3.0 MPa, while the pipe in Comparative Example 2 failed at 0.65 MPa.

[0042] The degree of crosslinking of the finished product of Comparative Example 3 was 44, because the activity of dibutyltin dilaurate at room temperature was not as good as that of dioctyltin dilaurate in the embodiments of the present invention.

[0043] The degree of crosslinking of the finished product in Comparative Example 4 was 28. The reason for this was the lack of tetramethylguanidine. The activity of using dioctyltin dilaurate alone is generally low. Tetramethylguanidine is a super base. Although the amount used is small, it can significantly increase the crosslinking speed.

[0044] Comparative Example 5 The product used in this comparative example is PAP1 (polyethylene / aluminum alloy / heat resistant polyethylene composite pipe).

[0045] Comparative Example 6 The product used in this comparative example is RPAP3 (heat-resistant polyethylene / aluminum alloy / heat-resistant polyethylene composite pipe).

[0046] Comparative Example 7 The product used in this comparative example is PPAP4 (random polypropylene / aluminum alloy / random polypropylene composite pipe).

[0047] Comparative Example 8 The product used in this comparative example is XPAP2 (cross-linked polyethylene / aluminum alloy / cross-linked polyethylene composite pipe).

[0048] Test Example 2 The pipes of the examples and comparative examples 5-8 (produced by Aikon Enterprise Group (Zhejiang) Co., Ltd.) were subjected to performance testing, and their extreme operating temperatures were tested.

[0049] Experimental Method: After sealing the pipe to be tested with end-sealing furniture, the inside of the pipe was filled with water and placed in a 90℃ environment to test the failure time. The hydrostatic pressure was 1.75MPa. If the failure time was less than 165 hours, the test temperature was reduced by 10℃; if the failure time was greater than 165 hours, the test temperature was increased by 10℃. Following this method, if the pipe did not fail after 165 hours, but failed within 165 hours after increasing the temperature by 10℃, then this temperature is the limit of its service life.

[0050] The results are shown in Table 1.

[0051] Table 1

[0052] As can be seen from Table 1, the pipes prepared according to the embodiments of the present invention can significantly increase the operating temperature and can be applied to fields with higher working conditions.

[0053] Application examples Table 2 shows the specifications and cross-linking properties of the composite pipes of Examples and Comparative Example 8. The burst pressure refers to the pressure that is continuously increased at 95°C until the pipe bursts. The pressure at the moment of bursting is recorded as the burst pressure.

[0054] The results are as follows: Table 2

[0055] As can be seen from Table 2, the traditional cross-linked polyethylene composite pipe of Comparative Example 8 requires hot water at 95°C for more than 12 hours to achieve the cross-linking degree of 65. The composite pipe (cross-linked cross-linked polyisobutylene / aluminum alloy / cross-linked cross-linked polyisobutylene composite pipe) prepared by the present invention at room temperature can achieve efficient self-catalytic cross-linking at room temperature and can achieve a cross-linking degree of greater than 65 after natural storage for 12 hours.

[0056] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A highly efficient self-catalyzing cross-linked polyisobutylene composite material at room temperature, characterized in that, It includes silane-grafted polyisobutylene and a room-temperature crosslinking catalyst in a mass ratio of 85-95:3-8; The silane-grafted polyisobutylene comprises, by weight, the following raw materials: 87-97 parts polyisobutylene, 1.05-3.0 parts graft modifier, 0.03-0.10 parts initiator, 2.0-5.0 parts antioxidant, 1.33-3.38 parts brightener, 0.03-0.30 parts polymerization inhibitor; The room-temperature crosslinking catalyst comprises, by weight, the following raw materials: 80-95 parts polyisobutylene, 3.0-5.0 parts antioxidant, 1.3-4.5 parts lubricant, 0.05-0.30 parts dioctyltin dilaurate, 0.01-0.05 parts tetramethylguanidine, and 0.05-0.16 parts hydrophilic agent.

2. The highly efficient self-catalytic cross-linked polyisobutylene composite material at room temperature as described in claim 1, characterized in that, The grafting modifier is trimethoxyvinylsilane / vinyltriisopropoxysilane and isopropyltris(dioctylpyrophosphate)titanate in a mass ratio of 0.05-1.5:1-1.

5. The initiator is di-tert-butylperoxyisopropylbenzene or 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane.

3. The highly efficient self-catalyzing cross-linked polyisobutylene composite material at room temperature as described in claim 1, characterized in that, The antioxidant is tris[2,4-di-tert-butylphenyl] phosphite and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] in a mass ratio of 1:

1. The brightener is high-density oxidized polyethylene wax, low molecular weight polytetrafluoroethylene micro powder, and zinc stearate in a mass ratio of 0.5-1.5:0.03-0.08:0.8-1.

8.

4. The highly efficient self-catalyzing cross-linked polyisobutylene composite material at room temperature as described in claim 1, characterized in that, The polymerization inhibitor is hydroquinone or tert-butylcatechol; The lubricant is high-density oxidized polyethylene wax and zinc stearate in a mass ratio of 0.1-2:1.2-2.

5.

5. The highly efficient self-catalyzing cross-linked polyisobutylene composite material at room temperature as described in claim 1, characterized in that, The hydrophilic agent is glycerol and sodium sulfate in a mass ratio of 2-8:3-8.

6. The highly efficient self-catalyzing cross-linked polyisobutylene composite material at room temperature as described in claim 1, characterized in that, The preparation method of the silane-grafted polyisobutylene is as follows: polyisobutylene, grafting modifier, initiator, antioxidant, brightener and polymerization inhibitor are mixed and stirred, and granulated in a parallel twin-screw extruder at a processing temperature of 190-210℃ to obtain silane-grafted polyisobutylene.

7. The highly efficient self-catalyzing cross-linked polyisobutylene composite material at room temperature as described in claim 1, characterized in that, The preparation method of the room temperature crosslinking catalyst is as follows: polyisobutylene, antioxidant, lubricant, dioctyltin dilaurate, tetramethylguanidine and hydrophilic agent are mixed and dried at 80-85℃ for 1-2 hours, and then granulated in a parallel twin-screw extruder at a processing temperature of 150-180℃ to obtain the room temperature crosslinking catalyst.

8. A method for preparing a highly efficient autocatalytic cross-linked polyisobutylene composite material at room temperature according to any one of claims 1-7, characterized in that, The preparation steps are as follows: silane-grafted polyisobutylene and room temperature crosslinking catalyst are mixed evenly in a mass ratio of 85-95:3-8 and extruded in a single screw extruder.

9. The application of the room-temperature highly efficient autocatalytic cross-linked polyisobutylene composite material according to any one of claims 1-7 in pipes.

10. The application as described in claim 9, characterized in that, The manufacturing process of the pipe is as follows: First layer: Cross-linked polyisobutylene composite material is extruded into a core tube; Second layer: After heating the core tube at 100℃ for 20 seconds, coat the surface with maleic anhydride-grafted polybutene hot melt adhesive with a thickness of 0.1-0.15mm. Third layer: The aluminum strip is rolled into a tube shape, wrapped on the hot melt adhesive of the second layer, and then formed into an aluminum tube by laser butt welding. Fourth layer: After the aluminum tube is heated by high frequency, maleic anhydride grafted polybutene hot melt adhesive is coated on the outer surface with a thickness of 0.1-0.15mm. Fifth layer: Cross-linked polyisobutylene composite material is used as the outer tube material, coated on the hot melt adhesive of the fourth layer, and then cooled and shaped to form a composite tube. After being corona treated, the composite pipes are inkjet printed and coiled to form finished products. After being stored naturally for 12 hours, the degree of cross-linking is greater than 65%.